Case Report: Four Cases of Panayiotopoulos Syndrome Evolving to Juvenile Myoclonic Epilepsy - Enoki, Hideo; Itamura, Shinji; Baba, Shimpei; Okanishi, Tohru; Fujimoto, Ayataka (Frontiers in Neurology, 2020)
Panayiotopoulos syndrome (PS) is a self-limited focal epilepsy appearing in childhood. Seizures in PS are self-limiting and do not usually continue into adulthood. Juvenile myoclonic epilepsy (JME) is the most common type of idiopathic generalized epilepsy, developing around puberty and continuing throughout adulthood. We describe four cases of PS in childhood in which JME developed in adolescence. Age at onset ranged from 4 to 8 years for PS, and 11 to 14 years for JME. JME developed after PS subsided, with the interval between last PS seizure and first JME seizure ranging from 1 to 10 years. No link between the two conditions has previously been described. Since PS is considered to show good prognosis and to be self-limiting, long-term observation has been considered unnecessary. No definitive factors were found to predict future evolution to JME in our series, so longer-term follow-up may be warranted for all PS patients.